2019
DOI: 10.1111/nuf.12405
|View full text |Cite
|
Sign up to set email alerts
|

A concept analysis: Emotional regulation of nurses

Abstract: Aim: To explore the concept of emotional regulation in nursing.Background: People are exposed to a variety of potentially emotion-provoking stimuli almost on a daily basis. The fact that these types of stimuli do not trigger full-blown emotions every time suggests that people are able to manage their own emotions through an internal process. The process is referred to as emotional regulation (ER).Nursing is a stressful and emotionally charged profession, yet the concept of ER is not well explored in the nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Additionally, emotion regulation had implications among nurses who were exposed to a variety of emotion-provoking conditions (Fasbinder et al, 2020). However, the literature reported how the regulation of emotions was limited to not only expressive suppression but also concerned cognitive reappraisal ones, increasing or decreasing in intensity, or modifying the quality according to objectives of the context (Salvarani et al, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Additionally, emotion regulation had implications among nurses who were exposed to a variety of emotion-provoking conditions (Fasbinder et al, 2020). However, the literature reported how the regulation of emotions was limited to not only expressive suppression but also concerned cognitive reappraisal ones, increasing or decreasing in intensity, or modifying the quality according to objectives of the context (Salvarani et al, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Early adaptation can predict depressive symptoms six months after stroke [35]. Emotional contro/emotional regulation is the process by which individuals influence the emotional that they have, when they have them, how they experience and express those emotions [49]. Emotional regulation is closely related to coping, emotional resilience, emotional intelligence, emotional expressiveness, and emotional energy.…”
Section: Improving Self-control and Stay Motivatedmentioning
confidence: 99%
“…Transition is the process of moving from one department to another, and it is often associated with sizable changes in the nurses’ goals, roles, and responsibilities [ 11 ], which may cause anxiety, fear, panic, stress, and other different emotional conditions. Emotional regulation is characterized as the nurses’ ability to modify their emotional state in order to support adaptive purpose behaviors [ 12 ]. For example, it was shown that nurses who felt emotional weariness had trouble managing or controlling their emotions at work [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emotional regulation is characterized as the nurses’ ability to modify their emotional state in order to support adaptive purpose behaviors [ 12 ]. For example, it was shown that nurses who felt emotional weariness had trouble managing or controlling their emotions at work [ 12 ]. On the other hand, studies confirm that more adaptive coping and greater resilience lead to greater work satisfaction and reduced fatigue [ 13 ].…”
Section: Introductionmentioning
confidence: 99%